Reproductive and developmental toxicity following exposure to organophosphate ester flame retardants and plasticizers, triphenyl phosphate and isopropylated phenyl phosphate, in Sprague Dawley rats. (23rd December 2022) - Witchey, Shannah K; Sutherland, Vicki; Collins, Brad; Roberts, Georgia; Shockley, Keith R; Vallant, Molly; Krause, Jeffrey; Cunny, Helen; Waidyanatha, Suramya; Mylchreest, Eve; Sparrow, Barney; Moyer, Robert; et al.
Abstract: Two organophosphate esters used as flame retardants and plasticizers, triphenyl phosphate (TPHP) and isopropylated phenyl phosphate (IPP), have been detected in environmental samples around the world. Human exposure primarily occurs via oral ingestion with reported higher concentrations in children. Currently, there are no data to evaluate potential risk from exposure to either TPHP or IPP during fetal development. These short-term perinatal studies in rats provide preliminary toxicity data for TPHP and IPP, including information on transfer to fetus/offspring and across the pup blood-brain barrier. In separate experiments, TPHP or IPP were administered via dosed feed at concentrations 0, 1000, 3000, 10 000, 15 000, or 30 000 ppm to time-mated Hsd:Sprague Dawley SD rats from gestation day (GD) 6 through postnatal day (PND) 28; offspring were provided dosed feed at the same concentration as their dam (PND 28–PND 56). TPHP- and IPP-related toxicity resulted in removal of both 30 000 ppm groups on GD 12 and 15 000 ppm IPP group after parturition. Body weight and organ weights were impacted with exposure in remaining dams. Reproductive performance was perturbed at ≥10 000 ppm TPHP and all IPP exposure groups. In offspring, both TPHP- and IPP-related toxicity was noted in pups at ≥10 000 ppm as well as reduction in bodyweights, delays in pubertal endpoints, and/or reduced cholinesterase enzyme activity starting at 1000 ppm TPHP or IPP. Preliminary internal dose assessment indicated gestational and lactational transfer following exposure to TPHP or IPP. These findings demonstrate that offspring development is sensitive to 1000 ppm TPHP or IPP exposure.